Genetics of Unverricht-Lundborg Myoclonus Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs, 1993)
Clinical and molecular genetic data on a family from the United States in which four of five sibs were affected with progressive myoclonus epilepsy of Unverricht-Lundborg type are reported from the University of Helsinki, Finland; National Cancer Institute, Bethesda, MD; and the VA Hospital, University of Florida, Gainesville, FL.